Histopathological study of non-infectious papulosquamous lesions of skin - Chabbi, Kartik; MS, Susmitha; Anupama YG; Dadapeer HJ; Ramesh Babu K (Asian Journal of Medical Sciences, 2022)
Background: Papulosquamous diseases are characterized by scaly papules and plaques with similar clinical picture which leads to diagnostic confusion. A definitive histopathological diagnosis is required for effective treatment of such diseases. Aims and Objectives: The aim of the study was to study the clinicohistopathological correlation of different non-infectious papulosquamous skin lesions. Materials and Methods: Skin punch biopsy specimens from 100 clinically diagnosed/suspected non-infectious papulosquamous skin diseases were received in the Department of Pathology at a tertiary care hospital. The specimens obtained were subjected to formalin fixation and paraffin embedding, stained with hematoxylin and eosin and studied. Results: A total of 100 cases were studied. The most common lesion was psoriasis (42) followed by lichen planus (40). Maximum numbers of cases were seen in the age group of 31–60 years (61%). Males (54%) were commonly affected. Positive clinicopathological correlation was observed in 85% cases. Conclusion: Contribution of histopathology is definitely significant in overcoming clinical diagnostic dilemma in certain papulosquamous disorders.